2014
DOI: 10.1007/s12105-014-0532-x
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Gland Tumor “Wishes” to Add to the Next WHO Tumor Classification: Sclerosing Polycystic Adenosis, Mammary Analogue Secretory Carcinoma, Cribriform Adenocarcinoma of the Tongue and Other Sites, and Mucinous Variant of Myoepithelioma

Abstract: This review is a continuation of suggested tumor additions to the next WHO Tumor Classification. The author will focus on four salivary gland entities that have recently become accepted in the literature as new neoplastic entities: sclerosing polycystic adenosis, mammary analogue secretory carcinoma, cribriform adenocarcinoma of the tongue and other sites, and mucinous variant of myoepithelioma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 47 publications
(54 reference statements)
1
32
0
Order By: Relevance
“…With regard to its etiology, some authors consider SPA to represent a pseudotumoral and inflammatory sclerosing process 3) . On the other hand, other studies have demonstrated a monoclonal origin for this lesion, thus corroborating a possible neoplastic origin 2,12) . In addition, because it resembles a fibrocystic lesion, breast adenosis, and different degrees of dysplasia, some authors consider SPA to be a low-grade malignant neoplasm 13) .…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…With regard to its etiology, some authors consider SPA to represent a pseudotumoral and inflammatory sclerosing process 3) . On the other hand, other studies have demonstrated a monoclonal origin for this lesion, thus corroborating a possible neoplastic origin 2,12) . In addition, because it resembles a fibrocystic lesion, breast adenosis, and different degrees of dysplasia, some authors consider SPA to be a low-grade malignant neoplasm 13) .…”
Section: Discussionsupporting
confidence: 74%
“…Although the growth pattern of the nodules in such cases is slow and painless, some patients have reported pain as a change in sensitivity, usually manifesting as a tingling sensation 2) .…”
Section: Discussionmentioning
confidence: 99%
“…In nearly two thirds of the reported cases, MASC presents as a painless, slow-growing mass involving the parotid gland, followed by the minor oral and submandibular salivary glands, with a slight male predominance. The age of presentation ranges from 13 to 78 years with the mean age being in the 5th decade [14]. The current cytology literature is limited to a few reported cases [1,3,4,5,6,7,8,9,10,11,12,13].…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have shown that CASGs and LGPAs are associated with higher risk of regional and distant metastases, compared with the classical PLGAs (5, 810, 12). Therefore, several groups have proposed to classify LGPA and CASG as entities distinct from PLGA to emphasize their aggressive behaviors (810, 13). These tumors were included as variants of PLGA in the WHO classification of 2005 (2) but the controversies remain unresolved and uniform diagnostic criteria are yet to be formed.…”
Section: Introductionmentioning
confidence: 99%